1991
DOI: 10.1148/radiology.180.3.1714612
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnetic localization of ventricular arrhythmias.

Abstract: The magnetic fields caused by electrical activity of the human heart can be coherently measured with a highly sensitive, multichannel, superconducting quantum interference-device system and can enable noninvasive localization of the underlying electrical activity. The magnetocardiograms (MCGs) of 10 patients with spontaneous premature ventricular complexes (PVCs), three patients with ventricular tachycardia (VT), and four healthy subjects with induced paced beats were recorded for 2-15 minutes. After correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…The development of an amagnetic, MR-compatible pacing catheter permitted the exact verification of the localization accuracy of the combined method of multichannel magnetocardiography and MR imaging. Our investigations of paced and spontaneous arrhythmias could demonstrate that multichannel magnetocardiography constitutes a method that permits the non-invasive localization of arrhythmogenic tissues in the heart with an error of less than 10 mm [16][17].…”
Section: Discussionmentioning
confidence: 81%
“…The development of an amagnetic, MR-compatible pacing catheter permitted the exact verification of the localization accuracy of the combined method of multichannel magnetocardiography and MR imaging. Our investigations of paced and spontaneous arrhythmias could demonstrate that multichannel magnetocardiography constitutes a method that permits the non-invasive localization of arrhythmogenic tissues in the heart with an error of less than 10 mm [16][17].…”
Section: Discussionmentioning
confidence: 81%
“…Non-invasive localization of cardiac arrhythmias, presently the most important application of magnetocardiography, has been reported before [6,8,[19][20][21]. for the current source and the volume conductor), individual patient positioning and the coordinate transfer between MCG and MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not until the availability of multichannel SQUID systems installed in magnetically shielded rooms that the registration quality was sufficient for the development of clinical applications [7][8][9]. Making use of the available technology, we investigated the applicability and accuracy of multichannel magnetocardiographic recordings for non-invasive 3-dimensional localization in phantom and patient studies, by comparison to established reference methods, and, as a gold standard, by the confirmation of localization results through successful high frequency catheter ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the orientation of stimulated ectopic beats was calculated from the magnetic field distribution and verified by MRI. The authors concluded that multichannel magnetocardiographic studies enable the completely non-invasive localization of ventricular arrhythmias [61]. The results were obtained in parallel by other investigators [62].…”
Section: Rozkład Prądów Nasierdziowych U Pacjenta Z Ciasnym Zwężenimentioning
confidence: 74%
“…Pioneering work concerning the exactness of biomagnetic localization was done by Moshage et al [61]. The authors studied patients with ventricular arrhythmias by combining MCG data with magnetic resonance imaging (MRI).…”
Section: Rozkład Prądów Nasierdziowych U Pacjenta Z Ciasnym Zwężenimentioning
confidence: 99%